2005
DOI: 10.1073/pnas.0502041102
|View full text |Cite
|
Sign up to set email alerts
|

The binding of the ubiquitous transcription factor Sp1 at the locus control region represses the expression of β-like globin genes

Abstract: To investigate the function of transcription factor Sp1 in ␤-like globin gene activation, we analyzed the recruitment of Sp1, fetal Krü ppel-like factor 2 (FKLF2), and related factors at the human ␤-globin locus in a human fetal liver and mouse erythroleukemia hybrid cell (A181␥ cell) that contains a single copy of human chromosome 11. Sp1 binds at the GT boxes of the cis-elements throughout the ␤-locus, but it is phosphorylated and lost over DNase I hypersensitive site (HS)2, HS3, HS4, and the human ␤-globin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The ubiquitously expressed SP1 zinc finger protein is the first described member of the Krüppel-like factors that bind to the consensus sequences of the GC and GT boxes (26). Two previous studies reported that SP1 could repress ␤-like globin gene transcription by binding to the LCR and globin promoter during erythroid differentiation (14,15). These data suggest that miR-23a and miR-27a regulate ␤-like globin gene expression by targeting KLF3 and SP1, respectively.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The ubiquitously expressed SP1 zinc finger protein is the first described member of the Krüppel-like factors that bind to the consensus sequences of the GC and GT boxes (26). Two previous studies reported that SP1 could repress ␤-like globin gene transcription by binding to the LCR and globin promoter during erythroid differentiation (14,15). These data suggest that miR-23a and miR-27a regulate ␤-like globin gene expression by targeting KLF3 and SP1, respectively.…”
mentioning
confidence: 75%
“…5F). SP1 is a ubiquitously expressed zinc finger protein that has been reported to repress ␤-like globin gene transcription through binding to HS1, HS2, HS3, HS4, HS5, and regions of the ε-, ␥-, and ␤-globin gene promoter during A␥181 cell erythroid differentiation (15) (Fig. 5G).…”
Section: Repression Of Klf3 Is Required For the Mir-23a-mediated Enhamentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that Sp1 regulates Pemt gene expression in 3T3-L1 cells by acting as a transcriptional repressor. Sp1 has previously been shown to promote repression of target genes by recruiting histone deacetylases both directly (37) and indirectly (36,40,41) to specific promoters. Typically, Sp1 physically interacts with several nuclear proteins in a dynamic complex to perform transcriptional repression (42) as well as de-repression and activation (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse embryo, there is robust developmental expression of KLF13 in the heart, cephalic mesenchyme, dermis, and epithelial layers of the gut and urinary bladder [50]. There are a number of reports describing the important role of KLF13 in the transcriptional regulation of erythroid gene expression [51,52] and its critical role in the induction of RANTES expression in activated T-lymphocytes [48,53].…”
Section: Klf13mentioning
confidence: 99%